Exploring practitioner constraints in advancing to more senior corporate communication roles - Tanya le Roux; Benita Steyn (Communicare)
The primary objective of this phenomenological exploratory study was to explore the constraints experienced by selected corporate communication practitioners in the South African banking industry in advancing to more senior corporate communication roles. The literature review indicated various individual, organisational and communication profession constraints experienced by practitioners. In the empirical study, additional constraints, such as organisational politics, the length of time spent in the organisation, the practitioner’s lack of networking and relationship building skills, the lack of overseas experience, and the lack of the standardisation of communication practitioner deliverables, were identified